St. Vincent and the Grenadines : 2018 Article IV Consultation-Press Release; Staff Report and Statement by the Executive Director for St. Vincent and the Grenadines. (IMF Staff Country Reports; Country Report ;, 2019)
This Article IV Consultation highlights that following the opening of a modern international airport, signs of an economic recovery have emerged, with increased direct flights from major cities in the United States and Canada and renewed interests from foreign investors in tourism projects. The overall fiscal balance has improved over the past few years, and the debt to GDP ratio fell in 2017 for the first time since 2007. However, despite these positive developments, St. Vincent and the Grenadines faces challenges in sustaining the growth momentum over the longer-term. Like other Caribbean economies, its high exposure to natural disasters, limited land, narrow production and exports base, weak business competitiveness, and limited physical and human capital constrain potential growth. The financial system remains broadly stable but has vulnerable spots in the non-bank financial sector. It is important to implement structural reforms to foster private sector activity, by improving the investment environment and strengthening physical and human capital.